Temporal Planning while the Clock Ticks - Cashmore, Michael; Coles, Andrew; Cserna, Bence; Karpas, Erez; Magazzeni, Daniele; Ruml, Wheeler (Proceedings of the International Conference on Automated Planning and Scheduling, 2018)
One of the original motivations for domain-independent planning was to generate plans that would then be executed in the environment. However, most existing planners ignore the passage of time during planning. While this can work well when absolute time does not play a role, this approach can lead to plans failing when there are external timing constraints, such as deadlines. In this paper, we describe a new approach for time-sensitive temporal planning. Our planner is aware of the fact that plan execution will start only once planning finishes, and incorporates this information into its decision making, in order to focus the search on branches that are more likely to lead to plans that will be feasible when the planner finishes.